Hernio-abdominoplasty with or without Scarpa's Fascia Preservation for Ventral Hernia and Abdominal Wall Deformity. Issue 7 (July 2019) - Eltantawy, Mahmoud; Elshobaky, Ayman; Thabet, Waleed; Emile, Sameh; El-Said, Mohammed; Elshobaky, Mohamed Taher; Mahmoud, Sabry Ahmed
Abstract : Background: Scarpa's fascia preservation plays a great role in decreasing the volume of wound drainage and reducing seroma after abdominoplasty. This study aimed to assess the role of Scarpa's fascia preservation in patients with ventral hernias associated with abdominal wall deformity who underwent concomitant hernio-abdominoplasty in terms of early and late postoperative outcome and quality of life. Methods: Patients with ventral hernia and abdominal wall deformity underwent combined hernio-abdominoplasty. Patients were randomly allocated to 1 of 2 equal groups: group I underwent Scarpa's fascia preserving hernio-abdominoplasty and group II underwent hernio-abdominoplasty with removal of Scarpa's fascia. Volume of drainage, time to remove drains, return to work, and complications were recorded. Results: Fifty patients (49 female) were included to the study. Both groups had comparable operation time, pain score, and complication rate (24% versus 40%, P = 0.36). The mean total volume of postoperative drainage was significantly lower in group I than group II (686 ± 183.5 versus 1410.8 ± 371.6 ml; P < 0.0001). Group I had earlier drain removal (11.6 ± 1.9 versus 20.5 ± 4.2 days, P < 0.0001) and earlier return to work (16.4 ± 2.3 versus 23.3 ± 3.8 days, P < 0.0001) than group II. There were no recorded cases of hematoma or hernia recurrence after repair. Conclusion: Scarpa's fascia preservation in combined ventral hernia repair and abdominoplasty was associated with significantly lower volume of postoperative drainage, earlier removal of drains, and similar recurrence rate to hernio-abdominoplasty with removal of Scarpa's fascia.